Сужение ультрамягких рентгеновских спектров и изменение зонной энергии электронов вследствие диспергирования порошков рутилоподобного TiO2 до наноразмеров - Бекенев, В.Л.; Зарко, В.И.; Зауличный, Я.В.; Фоя, А.А. ("Доповіді НАН України", 2007)
The investigation of X-ray OKα- and TiLα-emission bands in coarse-(‾d > 5 μm) and nanopowders (‾d = 107 and 10 nm) reveals the narrowing and a change of their shape, that is due to the energy redistribution of valence electrons in the Op-states after the break of atomic bonds during the dispersion of the material to nanosizes. It is shown that the band energy increases by 2% when the average size of particles decreases to 107 nm and by 18% after it decreases to 10 nm.